PENGARUH KEPEMIMPINAN, MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI NEGERI SIPIL (STUDI KASUS DI LINGKUNGAN PEMERINTAH KECAMATAN KRAMAT JATI, KOTA ADMINISTRASI JAKARTA TIMUR) - Arif, Muhamad . (Indikator: Jurnal Ilmiah Manajemen dan Bisnis, 2019)
Abstract : This study aims to analyze the influence of leadership, motivation and work discipline through employee servant of government performance. The sampling used as many as 90 employees of civil servant of first district at Kramat Jati. This study are observed in August until September 2019 at first district Kramat Jati, East Jakarta. The analyctical tool used smartPLS volume 3.2.8 (Partial Least Square). The result showed the influence of variable leadership andÂ  motivation are positive and significant effect for employee performance directly. The leadership directly had positive influence but insignificantly to employee performance. Motivation has positive direct and significant influence to employee performance. In a while, leadership and motivation with work discipline as an intervening variable, indirect has positive influence but insignificant to employee performance for civil servant in first district Kramat Jati, East Jakarta.